Show that cosh^2(x)-sinh^2(x)=1

In exponential form, sinh^2(x)=1/4(e^2x+e^-2x-2), cosh^2(x)=1/4(e^2x+e^-2x+2). Therefore cosh^2(x)-sinh^2(x)=1/4(2-(-2))=4/4=1, as required. 

Related Further Mathematics A Level answers

All answers ▸

A curve has polar equation r = 1 + cos THETA for 0 <= THETA <= 2Pi. Find the area of the region enclosed by the curve


If the complex number z = 5 + 4i, work out 1/z.


Prove that "6^n + 9" is divisible by 5 for all natural numbers.


If 0<x<1, find the following sum: S = 1+2*x + 3*x^2 + 4*x^3 + ...


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences